Sub-Zones in the Euro Area as Optimum Currency Areas - Bogdan WLODARCZYK; Paulina PUKIN (Communications of International Proceedings, 2020)
Researchers assert that the euro area is not an optimum currency area (OCA). Hence, the currency union is characterized by considerable vulnerability of economies to asymmetric shocks and the ECB’s monetary policy is unable to counteract negative consequences of the implementation of the common currency. However, researchers highlight that some of the EU countries could become an optimum currency area. The objective of this study was to verify the assertion put forth by B. Eichengreen and T. Bayoumi, implicating the existence of several groups of countries in the EU (to which two other sub-areas were added: Central Eastern Europe, and Cyprus and Malta) which can be distinguished based on macroeconomic criteria. In line with the assumptions made by economists, the sub-zones could satisfy the criteria devised in the OCA theory, as suggested by the main proponents of this concept, that is the convergence of business cycles, labour mobility, inflation and liberal economy. The research results implicate that the analyzed euro sub-zones do not fully satisfy these criteria. However, three countries, Germany, France and the Netherlands, could create a sub-zone of optimum currency area.
Keywords: the euro; the euro area; optimum currency areas